The type of Setophaga ruficoronata (Kaup 1851) is a hybrid: implications for the taxonomy of Myioborus warblers (Passeriformes: Parulidae) - Cuervo, Andrés M.; Arias, Laura N. Céspedes (Zootaxa, 2023)
Hybridization, rapid diversification, and uncertainties surrounding type specimens add complexity to the already intricate taxonomy of high Andean Myioborus warblers of northern South America. In this study, we propose a reassessment of species boundaries within M. ornatus and M. melanocephalus, drawing on comparisons of name-bearing types. We also consider insights from a recent study of a hybrid zone in southern Colombia and northern Ecuador. We present three species delimitation alternatives that offer improved clarity compared to the current taxonomy, and discuss the rationale behind recognizing chrysops and bairdi as distinct species while redefining the species ornatus and melanocephalus, given the available evidence.